Movement of Calcium Ions and their Role in the Activation of Platelets - Massini, P; Käser-Glanzmann, R; Lüscher, E F (Thrombosis and Haemostasis, 1978)
The increase of the cytoplasmic Ca-concentration plays a central role in the initiation of platelet activation. Four kinds of movements of Ca-ions are presumed to occur during this process: a) Ca-ions liberated from membranes induce the rapid shape change, b) Vesicular organelles release Ca-ions into the cytoplasm which initiate the release reaction, c) The storage organelles called dense bodies, secrete their contents including Ca-ions to the outside during the release reaction, d) At the same time a rearrangement of the plasma membrane occurs, resulting in an increase in its permeability for Ca-ions as well as in an increase in the number of Ca-binding sites.Since most processes occurring during platelet activation are reversible, the platelet must be equipped with a mechanism which removes Ca-ions from the cytoplasm. A vesicular fraction obtained from homogenized platelets indeed accumulates Ca actively. This Ca- pump is stimulated by cyclic AMP and protein kinase; it may be involved in the recovery of platelets after activation.It becomes increasingly clear that the various manifestations of platelet activation are triggered by a rise in the cytoplasmic Ca2+-concentration. The evidence for this and possible mechanisms involved are discussed in some detail in the contributions by Detwiler et al. and by Gerrard and White to this symposium. In this article we shall discuss four different types of mobilization of Ca-ions which occur in the course of the activation of platelets. In addition, at least one transport step involved in the removal of Ca2+ must occur during relaxation of activated platelets.